Examining the Role of a Functional Deficiency of Iron in Lysosomal Storage Disorders with Translational Relevance to Alzheimer’s Disease - Steven M. LeVine (Cells, 2023)
The recently presented Azalea Hypothesis for Alzheimer’s disease asserts that iron becomes sequestered, leading to a functional iron deficiency that contributes to neurodegeneration. Iron sequestration can occur by iron being bound to protein aggregates, such as amyloid β and tau, iron-rich structures not undergoing recycling (e.g., due to disrupted ferritinophagy and impaired mitophagy), and diminished delivery of iron from the lysosome to the cytosol. Reduced iron availability for biochemical reactions causes cells to respond to acquire additional iron, resulting in an elevation in the total iron level within affected brain regions. As the amount of unavailable iron increases, the level of available iron decreases until eventually it is unable to meet cellular demands, which leads to a functional iron deficiency. Normally, the lysosome plays an integral role in cellular iron homeostasis by facilitating both the delivery of iron to the cytosol (e.g., after endocytosis of the iron–transferrin–transferrin receptor complex) and the cellular recycling of iron. During a lysosomal storage disorder, an enzyme deficiency causes undigested substrates to accumulate, causing a sequelae of pathogenic events that may include cellular iron dyshomeostasis. Thus, a functional deficiency of iron may be a pathogenic mechanism occurring within several lysosomal storage diseases and Alzheimer’s disease.